2000
DOI: 10.1038/sj.ijo.0801130
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipolysis and hormone-sensitive lipase expression caused by procyanidins in 3T3-L1 adipocytes

Abstract: OBJECTIVE: To ®nd out whether lipid stores are in¯uenced by phenolic compounds in wine. DESIGN: Differentiated 3T3-L1 cells were treated with catechin, epicatechin or procyanidin extracts with different degrees of polymerization at 150 m mM for different periods of time (0.5 ± 24 h). SUBJECTS: Cell line 3T3-L1. MEASUREMENTS: Cellular viability, glycerol-3-phosphate dehydrogenase activity, glycerol release in the medium, HSL mRNA levels, triacylglycerols and protein. RESULTS: Catechin, epicatechin and procyanid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 40 publications
6
60
0
Order By: Relevance
“…The underlying mechanism could be an increased lipolysis. Ardevol et al (2000) found the same result in vitro, only by incubating 3T3-L1 cells with grape seed, lipolysis was favored and biosynthesis inhibited, thus degrading fat stores. The mechanism of grape seed in the short term could be, as Tebib also suggested, a delayed absorption of the diet, which might support sustained satiety while subjects ingest less food.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The underlying mechanism could be an increased lipolysis. Ardevol et al (2000) found the same result in vitro, only by incubating 3T3-L1 cells with grape seed, lipolysis was favored and biosynthesis inhibited, thus degrading fat stores. The mechanism of grape seed in the short term could be, as Tebib also suggested, a delayed absorption of the diet, which might support sustained satiety while subjects ingest less food.…”
Section: Discussionsupporting
confidence: 58%
“…With respect to the mechanism related to the possible effect of grape-seed extract, in animal models the polyphenols present in grape seed have shown to reduce food intake (Tebib et al, 1996;Wielinga et al, 2002) and to prevent weight gain (Tebib et al, 1996). In vitro experiments showed that these polyphenols stimulate lipolysis (Tebib et al, 1996;Ardevol et al, 2000), which is hypothesized to be particularly effective in overweight subjects who might show a reduced lipolysis (Fisher et al, 2002). Increased postprandial lipolysis may increase hepatic fat oxidation (Surina et al, 1993;Westerterp-Plantenga et al, 1999) and, thus, may affect satiety (Kamphuis et al, 2003;Langhans & Scharrer, 1987;McCarty & Scharrer, 1994;Scharrer, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…10 Briefly, postconfluent cells were induced to adipocyte differentiation (day 0) with 0.25 mmol/l dexamethasone, 0.5 mmol/l 3-isobutyl-methylxanthine, and 5 mg/ml insulin in 10% FBS/supplemented DMEM; after 48 h (day 2) cells were switched to 10% FBS/ supplemented DMEM containing only insulin, and at day 4 insulin was removed.…”
Section: Methodsmentioning
confidence: 99%
“…1,6,7 However, there is little information about their effects on adipocytes. 6,8,9 Few studies have focused on the action of procyanidins, an oligomeric class of flavonoids, in the adipose cell 10 or on the relationship between procyanidins and the adipose differentiation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation